The development of bacterial cellulose biomaterials using the material design-driven approach for packaging industry / Fadzli Irwan Bahrudin, Liew Yong Kian and Zati Hazira Ismail - Bahrudin, Fadzli Irwan; Kian, Liew Yong; Ismail, Zati Hazira (Universiti Teknologi MARA, Perak, 2022)
Alternative renewable materials are a possible solution to the rapid depletion of non-renewable resources. Within the renewable materials category, living organisms have been utilised in sustainable material projects. Although the projects are currently speculative, the possibility of utilising living organisms offers an appealing sustainability advantage for product design. Notably, their ability to 'self-build' enables them to become the co-maker of the output materials or products effectively. One of the promising lab-grown materials developed and utilised in product design is bacterial cellulose. Many researchers and designers have focused on improving the cultivation process and the feasibility of the materials for targeted product applications. However, much research is still needed to fill the void of knowledge in developing biomaterials for product design. This paper presents an early development of novel bacterial cellulose biomaterials and their applications using the Material Design Driven (MDD) framework. In this research, three bacterial cellulose biomaterials with unique experiential qualities have been produced through the approach. Notably, the research highlights the innovative potential of bacterial cellulose as a packaging material by incorporating plant fibres as the reinforcement agent and imprinting artificial texture on the material surface.